2015
DOI: 10.15640/jpesm.v2n2a13
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Anthropometric and Skill Data to Identify Talented Adolescent Team Handball Athletes

Abstract: Objectives: The purpose of this study was to detect differences between selected and unselected young handball athletes following a talent selection program, and to identify those characteristics that could predict young athletes' selection in such programs. Methods: The sample consisted of 129 male young players all invited to train in youth pro-selection groups. Variables included height, body mass, body mass index, 30m running speed, standing long jump, hand grip strength, ball velocity, flexibility, agilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…Meanwhile the body height and the minimum breadth of the hand) were found to be significantly correlated in the multiple regression model analysis. In accordance with the present results, previous studies have demonstrated that height [29,30,31], BMI [32,33,34] and the length and dimensions of the forearm, arm, and hands were significantly correlated with handgrip strength [35,36,37].…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile the body height and the minimum breadth of the hand) were found to be significantly correlated in the multiple regression model analysis. In accordance with the present results, previous studies have demonstrated that height [29,30,31], BMI [32,33,34] and the length and dimensions of the forearm, arm, and hands were significantly correlated with handgrip strength [35,36,37].…”
Section: Discussionsupporting
confidence: 93%
“…Mohamed et al (2009) also reported significant differences between elite and non-elite 15year-old male players in standing long jump, vertical jump, and hand grip strength. A recent study that detected differences between selected and nonselected Greek adolescent male handball players stated the superiority of selected athletes in stature, ball throwing velocity, standing long jump, aerobic capacity, 30 m sprint, agility and maximal isometric hand grip strength, with ball throwing velocity demonstrating the strongest relationship with the discriminant function (Palamas et al, 2015). Overall, previously existing studies suggest that the explosive muscle power of upper and lower limbs, as recorded by ball throwing velocity and jump tests, is the most important component that discriminates successful from less successful male and female athletes (Current study; Lidor et al, 2005;Matthys et al, 2011;Mohamed et al, 2009;Palamas et al, 2015;Zapartidis et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature there exist very few studies relating to the assessment of talented young boys (Lidor et al, 2005;Matthys et al, 2011;Mohamed et al, 2009;Palamas et al, 2015;Zapartidis et al, 2009) and even fewer studies on girls (Lidor et al, 2005;Zapartidis et al, 2009). By investigating the profile of adolescent female players, we can define the attributes that contribute to a player's selection for the team and add the data of the present study to the international literature to assist in female talent identification and development.…”
Section: Introductionmentioning
confidence: 95%
“…In a different study that used similar tests with adolescent handball players, the discriminant analysis predicted successful and less successful players with an overall accuracy of 73.6% (Palamas et al, 2015). Additionally, Özbay and Ulupınar (2020) found that laboratory tests performed with classical methods can accurately distinguish elite athletes from others with an overall accuracy of 65.4%.…”
Section: Discussionmentioning
confidence: 97%